ROLE OF BROWN ALGAE (SARGASSUM SP) AS ANTIBACTERIAL (PORPHYROMONAS GINGIVALIS) IN PERIODONTAL DISEASES - HERAWATI, DAHLIA; SUMANIK, B. CLARA (International Journal of Applied Pharmaceutics, 2019)
The main cause of periodontitis is bacterial porphyromonas gingivalis, which is an anaerobic gram-negative bacteria and is pathogenic because it destroys periodontal tissue. Brown algae (sargassum sp) is widely available in Indonesia waters, especially in the water of Maluku, and contains many minerals, fatty acids, phenols, alginates, fukosantin, alkaloids, steroids, saponins, flavonoids, tannins, carbohydrates, proteins, vitamins (A, B, C, D, E) and contains high levels of iodine that can be used as an antibacterial. This literature review aims to study the role of brown algae (sargassum sp) as an antibacterial (porphyromonas gingivalis) in periodontal disease. Brown algae (sargassum sp) can be used in traditional medicine, food, cosmetics/beauty, pharmacy and textile industries. This review found 3 different active compounds that act as antibacterial agents: phenols, flavonoids, and tannins. Therefore, brown algae (sargassum sp) can be used to inhibit the growth of porphyromonas gingivalis bacteria. The highest antibacterial content is found in brown algae (sargassum sp). Brown algae (sargassum sp) can be used as the basic treatment of periodontitis disease because it contains antibacterial substances such as phenols, flavonoids and tannins.